Tailoring tail-free nematogen of ethynylated-schiff base and its evaluation as solution-processable OLED emitting material - Lim, Soon Kit Julian; Rahamathullah, Rafizah; Sarih, Norazilawati Muhamad; Khairul, Wan Mohd (Elsevier, 2018)
A new rigid core dye comprised ESB-NO2 of chromophore moieties of acetylide (C≡C), Schiff base (C˭N) and nitro (NO2) was successfully synthesized to demonstrate tail-free nematogen as emitting material for organic light-emitting diode (OLED). The relationship between liquid crystal molecular structure, phase transition temperature and electroluminescence behaviour were evaluated. The mesomorphic properties of ESB-NO2 were identified via polarized optic microscopy (POM) which displayed nematic phase of Schlieren textures and their corresponding transition enthalpies were respectively recorded at 25.15 kJ mol−1. The photoluminescence behaviours of ESB-NO2 have been verified at λem,max = 538 nm where this emission are for its π→π * transition, intramolecular charge transfer (ICT) absorptions and fluoresce characters. Having ESB-NO2 as liquid crystalline material, OLED was constructed featuring single-layer indium tin oxide (ITO) coated substrate/ESB-NO2/Au via solution-casting method. The result revealed the single layer ESB-NO2 film displayed satisfactory electroluminescence with intense yellow emission under different direct current (DC) voltages supply. These findings indicate the practicability of designing tail-free nematogenic compounds as promising solution-processed OLED materials.